THE EFFECT OF FINANCIAL LITERACY, LIFESTYLE, AND SELF-CONTROL ON STUDENTS' FINANCIAL BEHAVIOR - Zahra Putri Nur Fadhila; Mahameru Rosy Rochmatullah (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2026)
This study examines the effect of financial literacy, lifestyle, and self-control on the financial behavior of accounting students in Surakarta. Using a quantitative approach, data were collected from 100 students through structured questionnaires with a five-point Likert scale, measuring financial literacy, lifestyle, and self-control. Financial literacy encompasses knowledge and skills in managing income, expenses, savings, investments, and credit, while lifestyle reflects consumption patterns, social habits, and personal preferences. Self-control represents the ability to regulate impulses and delay gratification. Data were analyzed using multiple linear regression after testing for validity, reliability, and classical assumptions to ensure accuracy and robustness. The results indicate that financial literacy and lifestyle significantly influence students’ financial behavior, with students who possess strong financial knowledge and controlled lifestyle habits demonstrating more responsible and directed financial management. In contrast, self-control was not found to have a significant effect. Collectively, the three variables explain 57.1% of the variation in financial behavior. The study highlights the importance of enhancing financial literacy and promoting balanced lifestyle habits among students to support better financial decision-making